It's All in the Mix: Blend-Specific Behavioral Response to a Sexual Pheromone in a Butterfly - Larsdotter-Mellström, Helena; Eriksson, Kerstin; Liblikas I, Ilme; Wiklund, Christer; Borg-Karlson, Anna K.; Nylin, Sören; Janz, Niklas; Carlsson, Mikael A. (Frontiers in Physiology, 2016)
Among insects, sexual pheromones are typically mixtures of two to several components, all of which are generally required to elicit a behavioural response. Here we show for the first time that a complete blend of sexual pheromone components is needed to elicit a response also in a butterfly. Males of the Green-veined White, Pieris napi, emit an aphrodisiac pheromone, citral, from wing glands. This pheromone is requisite for females to accept mating with a courting male. Citral is a mixture of the two geometric isomers geranial (E-isomer) and neral (Z-isomer) in an approximate 1:1 ratio. We found that both these compounds are required to elicit acceptance behaviour, which indicates synergistic interaction between processing of the isomers. Using functional Ca2+ imaging we found that geranial and neral evoke significantly different but overlapping glomerular activity patterns in the antennal lobe, which suggests receptors with different affinity for the two isomers. However, these glomeruli were intermingled with glomeruli responding to ,for example, plant-related compounds, i.e. no distinct subpopulation of pheromone-responding glomeruli as in moths and other insects. In addition, these glomeruli showed lower specificity than pheromone-activated glomeruli in moths. We could, however, not detect any mixture interactions among four identified glomeruli, indicating that the synergistic effect may be generated at a higher processing level. Furthermore, correlations between glomerular activity patterns evoked by the single isomers and the blend did not change over time.